2018
DOI: 10.1177/0739456x18793702
|View full text |Cite
|
Sign up to set email alerts
|

Public Housing Matters: Public Housing Policy in Sweden, the United States, and Israel

Abstract: During the past decade, many countries have returned to public housing to meet the demand for affordable housing. Using the Esping-Anderson typology, this study examines how differences in a country’s political economic regime influence the implementation and outcomes of public housing policies over time and the extent to which and how the differences change over time. The analysis focuses on Sweden, the United States, and Israel, representing three different regime types. In light of the renewed worldwide rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In contrast with many countries where the privatization of public housing reflected a reversal of housing policies, in Israel privatization was an ongoing policy long before the political shift, reflecting a preferential status of homeownership (Werczberger and Reshef 1993;Werczberger 1995). Privatization through the sale of public housing units to occupying renters intensified over the years and by 2015, the public housing sector constituted only 3% of the housing stock in Israel (Hananel et al 2018). Despite the important decline of this sector, it is not assumed to have had an important role in changing residential segregation within the Tel-Aviv MA, as most public housing were located in peripheral areas.…”
Section: Increasing Income Inequality In Israel and Socio-spatial Impmentioning
confidence: 99%
“…In contrast with many countries where the privatization of public housing reflected a reversal of housing policies, in Israel privatization was an ongoing policy long before the political shift, reflecting a preferential status of homeownership (Werczberger and Reshef 1993;Werczberger 1995). Privatization through the sale of public housing units to occupying renters intensified over the years and by 2015, the public housing sector constituted only 3% of the housing stock in Israel (Hananel et al 2018). Despite the important decline of this sector, it is not assumed to have had an important role in changing residential segregation within the Tel-Aviv MA, as most public housing were located in peripheral areas.…”
Section: Increasing Income Inequality In Israel and Socio-spatial Impmentioning
confidence: 99%
“…In the 1970s, as immigration declined, public-housing construction also dropped to an estimated 30% of all building starts. In this period, the government switched from supporting housing construction (supply side) to offering financial incentives for housing ownership through subsidized mortgages (demand side) [52].…”
Section: Third Decade-the 1970smentioning
confidence: 99%
“…This makes it very difficult for low-income people to put together the rent since it amounts to many months of income assuming there are no necessary expenditures like food for the family, transportation, education and health costs, among others. In a case study, those that cross this hurdle in Ghana were found to do so 'by the Grace of God' , friend and family support considering their irregular income that makes it difficult to pay monthly rent [4]. In another case study in Nigeria deploying multidimensional explanations of Lefebvre's theory of space describes how indigenous knowledge, residential history, culture of home ownership in the fatherland, motivation to be a landlord, provide for the family and be self-actualised were implicated when lowincome people utilised multiple resources to negotiate housing from the context of Ibadan, Nigeria [31].…”
Section: Housing Strategies Of the Low Incomementioning
confidence: 99%
“…Formal housing provision by government and or private organisations have direct beneficiaries: families who possess the willingness and ability to buy from the market, consultants, contractors, skilled and unskilled workmen in the construction industry, loan and credit institutions, building material producers and allied industries [3]. Public housing estates are known to be large homogenous enclaves of poverty in unattractive locations but are justified by supply side political idealists for affordable housing [4]. The political ideals that shape public housing are related to the political, social, legal and economic indices of different countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation